The worldsheet dual of the symmetric product CFT - Eberhardt, Lorenz; Gaberdiel, Matthias R.; Gopakumar, Rajesh (The journal of high energy physics, 2019)
A bstract Superstring theory on AdS 3 × S 3 × T 4 with the smallest amount of NS-NS flux (“ k = 1”) is shown to be dual to the spacetime CFT given by the large N limit of the free symmetric product orbifold Sym N T 4 . To define the worldsheet theory at k = 1, we employ the hybrid formalism in which the AdS 3 × S 3 part is described by the p s u 1 , 1 | 2 1 WZW model (which is well defined). Unlike the case for k ≥ 2, it turns out that the string spectrum at k = 1 does not exhibit the long string continuum, and perfectly matches with the large N limit of the symmetric product. We also demonstrate that the fusion rules of the symmetric orbifold are reproduced from the worldsheet perspective. Our proposal therefore affords a tractable worldsheet description of a tensionless limit in string theory, for which the dual CFT is also explicitly known.